Integrated framework for behaviour analysis in a process plant. (March 2016) - Panchal, Dilbagh; Kumar, Dinesh
Abstract: The fact that system reliability is influenced by numerous factors (model, assembling, installation, upkeep and use) makes it particularly challenging to identify, evaluate and anticipate the failure causes of system. To this effect, the current research work seeks to propose a quantitative and qualitative approach based integrated framework for the behaviour analysis of a process plant system. In the quantitative analysis, series/parallel combination of the considered system has been modelled using Petri net (PN) approach. Various reliability parameters were computed at different spreads and the system's behaviour is studied in crisp, fuzzy and defuzzified terms. Further, in order to improve system's availability and maintainability characteristics, an extensive qualitative analysis is performed using Root Cause Analysis (RCA) and Failure Mode and Effect Analysis (FMEA) for listing the various failure causes. Limitations of traditional FMEA in risk ranking of risky/critical components were overcome by using a Fuzzy Decision Making System (FDMS) and Grey Relation Analysis (GRA). The ranking results so obtained were compared with those of FMEA raking results for better decision making of risky components of the considered system. The framework has been employed to carry out the behavioural analysis of a real Water Treatment Plant (WTP) of a coal fired thermal power plant in North India. Graphical abstract: Highlights: A fuzzy methodology based integrated framework is proposed for behaviour analysis. Behaviour of WTP in a thermal power plant located in northern India is studied. PN has been used for system modelling. Reliability parameters of the system are computed at different spread. Risky components of the system are identified.